Transpirational cooling enhances grain yield and quality in heat-tolerant rice varieties - Mu, Qilin; Wang, Song; Liu, Yangxuan; Gao, Yuan; Liu, Wenyan; Okpala, Nnaemeka Emmanuel (Frontiers in Plant Science, 2025)
High temperatures during the grain-filling stage in rice often shorten grain-filling duration and accelerate maturity, typically reducing grain yield and quality. Leaf evaporative cooling via transpiration has been identified as an important adaptive mechanism for heat stress in rice. However, its relevance in evaluating varietal tolerance to heat during grain filling remains unclear. In this study, we assessed 28 newly bred, high-quality rice varieties to examine the extent of, and genotypic variation in, transpirational cooling and its effects on grain yield and quality under a staggered sowing system (S1 and S2). Our results showed that high temperatures significantly decreased 1,000-grain weight by 1.6 g and head rice rate by 6.7%, while increasing chalkiness by 3.3%. Cluster analysis grouped the varieties into three categories of heat tolerance: tolerant, intermediate, and susceptible. Under heat stress, heat-tolerant varieties maintained significantly lower leaf and panicle temperatures and exhibited higher stomatal conductance than heat-susceptible varieties during grain filling. These tolerant varieties also possessed higher stomatal density and total stomatal area. Furthermore, the change in 1,000-grain weight was negatively correlated with stomatal density, whereas the change in head rice rate showed a negative correlation with stomatal size. These findings suggest that varietal differences in heat tolerance during grain filling may parallel those observed at anthesis. Stomatal regulation of the canopy microenvironment may serve as a general physiological basis for varietal heat response in rice.